Komunikasi Visual Dalam Relief Karmawibhangga Candi Borobudur - Theodorus Aries Bryan Nugraha Setiawan Kusuma; Andry Hikari Damai; Andika Witono (Kemendikbud, 2020)
Relief is a 3-dimensional work of art carved on a rock that is related to religious teachings, both Hindu and Buddhist. Relief is used to show religious lessons to followers, one of the relief is the Karmawibhangga relief found in Borobudur Temple which explains about karma law lessons using the community background at that time. This research will discuss the problem of depicting life in Karmawibhangga relief which can be a visual communication medium in the Mataram Kuno era. The purpose of this research was to determine the role of reliefs related to the values of social life and the values of the great traditions of the Karmawibhangga relief at Borobudur Temple. This study used a descriptive analysis method with primary data based on direct observation of the Karmawibhangga relief object at Borobudur Temple, and secondary data in the form of photos from a collection from the Borobudur Temple Conservation Center, as well as literature studies. In visual communication, aesthetics is a part that contains aspects of natural configuration so as to convey the message as a whole. Relief Karmawibhangga is a visual communication medium that depicts life in the ancient Mataram era.